Primary nasal rhinosporidiosis - a ten year multicentre experience: what we know? - Rajendran, S.; Ashok, S. Shanmuga; Ramkumar, Thalapathy (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Rhinosporidiosis is a disease caused by Rhinosporidium seeberi that affects the mucous membranes primarily. Nose is the commonest organ to be involved. The authors of this paper with more than ten years of experience across various institutions in Tamil Nadu have analysed their cases and have found out that posterior lip of valve of hasner in the inferior meatus to be the site of attachment in primary nasal rhinosporidiosis irrespective of the endemicity of the region. Methods: This is a prospective study of seventy eight cases of primary rhinosporidiosis over a period of ten years (February 2009 to December 2019). Recurrent cases, those who did not come for follow up and who were operated under local anesthesia were not included in this study. All the patients (45) were subjected to endoscopic surgery for excision of the rhinosporidiosis under general anesthesia after informed written consent and sent for histopathological examination. Results: Most common age group being 25 to 50 years with male preponderance and the common site of occurrence is the posterior lip of valve of Hasner in the inferior meatus with seasonal variation with O+ve blood group preponderance. Most common clinical presentation is unilateral nasal obstruction. Conclusions: Rhinospordiosis is hyperendemic in Tiruvarur and Thiruvannamalai. The posterior lip of valve of hasner is the commonest site of attachment. Correct identification of the site of attachment and surgical excision with cauterisation prevents its recurrence.